CAUSAL RELATIONSHIP BETWEEN RENEWABLE ENERGY CONSUMPTION, ECONOMIC WELFARE, AND FOREIGN DIRECT INVESTMENT IN 6 ASEAN COUNTRIES - Giartikasari, Ghina; Nikensari, Sri Indah; Herlitah (Faculty of Economics and Business, Universitas Negeri Jakarta, 2022)
This is an empirical study on the causal relationship between renewable energy consumption, economic welfare, and foreign direct investment in 6 ASEAN countries over period 2005-2019 using Panel-Vector Error Correction Model. Specifically, the unit root test, cointegration test, Granger causality test, and vector error correction model are imployed for the estimations. Empirical results do not confirm feedback causality between renewable energy consumption and gross domestic product per capita. The empirical results indicate that there is causality, short-term and long-term relationship between renewable energy consumption, gross domestic product per capita, and foreign direct investment. Furthermore, the result for long run causality from renewable energy consumption have negative effect to gross domestic product per capita. Additionally, short- run causality from renewable energy consumption and gross domestic product per capita have positive effect to foreign direct investment. On the other hand, short-run causality from foreign direct investment have negative effect to gross domestic product per capita.